Shipping and warehouse area at Althouse Chemical Company plant (1952)
General view of the shipping and storage room at the Althouse Chemical Company manufacturing plant in Reading, Pennsylvania. Several rows of drums containing dyestuffs prepared for shipment fill the room. Various dye colors and lots numbers are visible on the sides of the drums. Employee Paul Leinbach is seen weighing the contents of a drum, presumably to determine the correct amount of dyestuffs. Based in Reading, Pennsylvania, the Althouse Chemical Company was founded in 1915 by C. Scott Althouse (1880-1970) as a small, family-owned firm specializing in fabric dyes of a superior quality and class. In 1954, the Crompton & Knowles Corporation of Worcester, Massachusetts acquired Althouse, which continued to operate as a division of Crompton & Knowles and a leader in the specialty dyes industry.
Keywords: Dye industry; Employees; Dyes and dyeing; Dyes and dyeing--Equipment and supplies; Althouse Chemical Company